2017
DOI: 10.4314/sajas.v47i4.14
|View full text |Cite
|
Sign up to set email alerts
|

Replacing maize grain with dried citrus pulp in a concentrate feed for Jersey cows grazing ryegrass pasture

Abstract: Dried citrus pulp (DCP) is a high-fibre by-product of the citrus industry. In total mixed ration (TMR) systems it has been shown to maintain a more stable ruminal environment, improving overall production compared with maize. The aim of the study was to determine the effects of stepwise replacement of maize with DCP in a concentrate supplement on milk yield, milk composition and rumen health of Jersey cows grazing ryegrass pasture. Sixty-eight lactating Jersey cows (μ ± SD; 84.5 ± 43.8 days in milk, 20.4 ± 3.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Thus, Zhao et al [49] reported no differences in rumen pH of Rusitec fermenters fed 50:50 forage:concentrate diets containing either 15% of pure citrus pectin or 15% of pure maize starch. Similarly, no differences in pH were reported when steers fed a tropical grass based diet were supplemented daily with 0, 1.5, or 2.5 kg of pelleted DCP [50], when DCP replaced maize in the concentrate fed to grazing cows [51], or when barley grains were totally replaced by DCP in a 50:50 forage:concentrate diet for dairy sheep [20]. Altogether, these results might indicate that the influence of DCP on rumen pH is more pronounced for high-concentrate than for medium-and high-forage diets.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, Zhao et al [49] reported no differences in rumen pH of Rusitec fermenters fed 50:50 forage:concentrate diets containing either 15% of pure citrus pectin or 15% of pure maize starch. Similarly, no differences in pH were reported when steers fed a tropical grass based diet were supplemented daily with 0, 1.5, or 2.5 kg of pelleted DCP [50], when DCP replaced maize in the concentrate fed to grazing cows [51], or when barley grains were totally replaced by DCP in a 50:50 forage:concentrate diet for dairy sheep [20]. Altogether, these results might indicate that the influence of DCP on rumen pH is more pronounced for high-concentrate than for medium-and high-forage diets.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, the differences in the crude fiber were observed between the whole C. limon and C. clementina fruits may largely be due to the difference in the citrus species (Audu et al, 2018). Dried whole citrus fruit is a rich source of fiber and when used as livestock feed in a total mixed ration (TMR) feeding scheme since it supplies a stable ruminal environment in ruminants, thereby improving animal productivity (Steyn et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Citrus fruits as a by-product can be gathered in large quantities and processed as a prospective periodic livestock feed source to improve animal production (Steyn et al, 2017). Conversely, there is merit in evaluating the utilization of whole citrus fruit as an alternative livestock feed resource in South Africa as it could proffer an alternative or complementary/supplementary feed ingredient for livestock farmers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucogenic-based ingredients consist of cereal grains and their milling by-products, molasses, beet and citrus pulps, roots and tubers such as cassava and potatoes and their by-products, and dried reclaimed bakery products (McDonald et al, 2002;Mosavi et al, 2012;Steyn et al, 2017). Fat increases the energy density of the diet (Schroeder et al, 2004), and in particular enhances plasma cholesterol, the major precursor for steroidogenesis, including luteal P 4 synthesis in postpartum cows .…”
Section: Introductionmentioning
confidence: 99%